2019
DOI: 10.1108/ijhcqa-08-2017-0153
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and improving the care pathway for children with autism

Abstract: Structured Abstract:Purpose: To describe current care pathways for children with autism including enablers and barriers, as experienced by health professionals, education professionals, and families in South Wales, UK. Design/Methodology/Approach: A mixed-methods approach using focus group discussions, creative writing workshops and visualisation using rich pictures. Findings: The experiences of the care pathways differed significantly across the three groups. Health professionals described the most rigidly-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
(18 reference statements)
0
30
0
1
Order By: Relevance
“…In the UK, the multi-disciplinary team approach is one of the assessment methods used for ASD diagnosis, although it is not available in all areas [3,64]. Research has shown that it is difficult to get a multi-disciplinary team together, especially when they span different disciplines such as education and health [19]. Therefore, telehealth may provide support and help to a specialist ASD team, allowing them to meet remotely and provide a diagnosis regardless of their locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, the multi-disciplinary team approach is one of the assessment methods used for ASD diagnosis, although it is not available in all areas [3,64]. Research has shown that it is difficult to get a multi-disciplinary team together, especially when they span different disciplines such as education and health [19]. Therefore, telehealth may provide support and help to a specialist ASD team, allowing them to meet remotely and provide a diagnosis regardless of their locations.…”
Section: Discussionmentioning
confidence: 99%
“…This is not only a cost to the family but also to the specialist healthcare teams who travel to reach different areas. Recent research found that healthcare and educational systems work independent from each other with little crossover of activity [19], therefore it may be difficult to get multi-disciplinary teams together, especially when they span different disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Improved communication between parents and teachers is needed (Azad and Mandell 2016). The advantages of integrated working between health, social care and education have been noted in the literature and were reiterated by project staff; particularly in giving the children consistency in the strategies used to overcome their difficulties (Hurt et al 2019). Future intervention projects should attempt to address the issue of home-school links more proactively.…”
Section: Post-diagnostic Support For Familiesmentioning
confidence: 99%
“…Their engagement and the joint forces of therapist, teacher and parents are expected to contribute to improve the level of care (cf. Hurt et al, 2017;Schothorst et al, 2009).…”
Section: Strenghts and Limitationsmentioning
confidence: 99%